2019
DOI: 10.1002/jmv.25386
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus shedding from breastmilk and mucosal sites in healthy postpartum women: A pilot study

Abstract: Mother‐to‐child cytomegalovirus (CMV) breastmilk transmission can occur in the postnatal period. In a pilot study, we measured daily CMV detection by polymerase chain reaction in breastmilk, vaginal, and saliva samples from nine healthy CMV‐seropositive postpartum women for 28 days. CMV was found in seven of nine women and 171 of 253 breastmilk samples (67.6%). In four women, all breastmilk samples were positive. CMV was less frequently detected in the vagina (39 of 258, 15.1%) and saliva (53 of 258, 20.5%). D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Furthermore, these mothers showed serological characteristics of a latent HCMV infection with high HCMV-IgG levels and high IgG-avidity and lack of IgM detection. Azenkot et al [41] found positive samples in a minority of vaginal secretions (three of nine mothers) and saliva (two of nine) but without viral DNAemia detection.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, these mothers showed serological characteristics of a latent HCMV infection with high HCMV-IgG levels and high IgG-avidity and lack of IgM detection. Azenkot et al [41] found positive samples in a minority of vaginal secretions (three of nine mothers) and saliva (two of nine) but without viral DNAemia detection.…”
Section: Discussionmentioning
confidence: 97%
“…Concerns about false positive results with these samples have been raised because virus transmission during breastfeeding may occur. Several articles reported the excretion of this virus in the breast milk of healthy women [ 22 , 23 ]. To prevent these false-positive during screening programs an approach would be to instruct health professionals to collect the sample before the first breastfeeding, although this is not always possible.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic spread of the pathogen then may lead to secondary lung infection. In addition to transplacental infection in utero (congenital), newborns are at increased risk for perinatal infection via exposure to secretions in the birth canal or ingestion of virus-containing breast milk [24]. Interestingly, neonates and infants exhibit protracted shedding of virus in urine and saliva [25].…”
Section: Clinical Problem—hcmv Pneumonitismentioning
confidence: 99%